ASN Willingness in Policy Implementation: A Study of Core Values and Motivation - M Ramadhi Utama; Slamet Widodo; Raniasa Putra (Universitas Muhammadiyah Ponorogo, 2026)
Researchers and practitioners have articulated that Organizational Factors and Individual Factors constitute pivotal elements in influencing the Willingness of Employees, specifically in the context of the State Civil Apparatus (ASN) to implement policies. The objective of this research was to assess the impact and quantify the extent to which the Core Values of ASN BerAKHLAK and ASN Motivation (Public Service Motivation) affect the willingness of ASNs to implement the policy regarding the utilization of the Integrated Discipline (I'DIS) application in the administration of ASN Discipline, both in a simultaneous and partial context. The sample population for this study comprised 67 ASNs employed within the Discipline Management Sub Division across 49 Personnel Working Units at Government Institutions situated within the jurisdiction of Regional Office VII of the Palembang National Civil Service Agency. The data were subjected to analysis through the application of Multiple Regression tests and Hypothesis testing utilizing SPSS Version 29.0. The findings from the analysis indicate that the Core Values of ASN BerAKHLAK and ASN Motivation collectively exert an influence on ASN's propensity to adopt the policy regarding the utilization of the I'DIS application in the management of ASN Discipline. Nevertheless, when examined individually, it is solely ASN Motivation that demonstrates a significant effect on ASN's willingness to implement the policy of employing the I'DIS application for the purposes of managing ASN Discipline.